Literature Review: The Influence of Internal Control Systems and the Role of Internal Audit on Good Corporate Governance: Finance - Josua Panatap Soehaditama; Nyoman Sawitri (Greenation International Journal of Economics and Accounting, 2023)
Internal Audit has the function of helping companies achieve their business goals by evaluating and improving the effectiveness of the company's internal control system, risk management and business processes. Internal audit is also responsible for making recommendations for changes and ensuring that the organization follows all applicable laws and regulations. Through the implementation of GCG principles, companies can ensure that the internal control system is implemented effectively and efficiently, and ensure that all stakeholders are respected and treated fairly. The relationship between this research is the importance for companies to develop and strengthen internal control systems, increase the effectiveness of internal audits, and ensure management's commitment to implementing good GCG practices in the company. This literature shows that the internal control system, the role of internal audit, and management commitment significantly influence Good Corporate Governance practices. Several studies show that implementing GCG principles helps companies increase transparency, accountability and compliance with organizational regulations.